SELEKSI KARYAWAN PADA POSISI ASSISTANT SUPERINTENDENT - Rislisa Rislisa; Mukhaira El Akmal (Universitas Muhammadiyah Tapanuli Selatan, 2018)
All organization or company needs human resources in carrying out every function of activity. The need of human resources is very important because in gaining superior human resources cannot be obtained easily; it takes a way to get the right labor to fill a certain position by selection. It is hoped that by doing this process, we will get reliable human resources, which are needed to meet the needs of the organization in the present and future. Selection activities are conducted in the framework of community service activities. The target of community service is to accompany the company so that prospective new employees who follow the selection process at the psychological test stage can complete all the test stages. The selection of superintendent assistant positions is done by the Psychology Test Method (to reveal aspects of intelligence, work attitude, and personality), Leaderless Group Discussion (LGD), and Psychological Interview. This test was followed by 203 participants. As a result of the whole process, 136 participants were graduated. Key words:selection, employees, assistant superintendent.